2009
DOI: 10.1177/0192623308329340
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicity and Environment: Immunodysregulation and Systemic Inflammation in Children

Abstract: Environmental pollutants, chemicals, and drugs have an impact on children's immune system development. Mexico City (MC) children exposed to significant concentrations of air pollutants exhibit chronic respiratory inflammation, systemic inflammation, neuroinflammation, and cognitive deficits. We tested the hypothesis that exposure to severe air pollution plays a role in the immune responses of asymptomatic, apparently healthy children. Blood measurements for markers of immune function, inflammatory mediators, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
58
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 71 publications
6
58
0
5
Order By: Relevance
“…The marked reduction of peripheral blood neutrophils observed in highly exposed Mexico City children in this work and in previous studies, along with high concentrations of endothelin-1, have been taken as strong evidence for endothelial activation and inflammation (4,6) Moreover, the increase in monocytes has been described upon exposure to particulate matter (49). An interesting association in this work is the positive relationship between body fat and the numbers of peripheral neutrophils, as well as between monocytes and IL-6 concentrations in keeping with the literature pointing to low-grade systemic infl ammation related to higher levels of body fat in children (50,51).…”
Section: Note: the Numerical Values Shown In The Table Represent Meansupporting
confidence: 68%
See 2 more Smart Citations
“…The marked reduction of peripheral blood neutrophils observed in highly exposed Mexico City children in this work and in previous studies, along with high concentrations of endothelin-1, have been taken as strong evidence for endothelial activation and inflammation (4,6) Moreover, the increase in monocytes has been described upon exposure to particulate matter (49). An interesting association in this work is the positive relationship between body fat and the numbers of peripheral neutrophils, as well as between monocytes and IL-6 concentrations in keeping with the literature pointing to low-grade systemic infl ammation related to higher levels of body fat in children (50,51).…”
Section: Note: the Numerical Values Shown In The Table Represent Meansupporting
confidence: 68%
“…TLR4 plays a critical role in the activation of IL-6 producing leukocytes (32) and LPS promotes osteoclast activity and bone resorption (37). Both associations are also very relevant in Mexico City where children are exposed to signifi cant concentrations of lipopolysaccharides associated with particulate matter (6). Since 85 % of the Mexican population lacks the Asp299Gly Toll-like receptor-4 (TLR-4) polymorphism associated with a blunted response to lipopolysacharide (Calderón-Garcidueñas personal data), most Mexican children will be responsive to LPS and the activation of TLR4.…”
Section: Note: the Numerical Values Shown In The Table Represent Meanmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last 20 years, exposure to fossil fuel combustion has attracted significant medical interest. Many studies have demonstrated that current levels of air pollutants contribute to cardiovascular and respiratory morbidity and mortality in adults and children (2,3,(12)(13)(14). We have analyzed air pollutant measurements in the Sao Paulo metropolitan area over the last 30 years, and observed that pollutant levels recorded at each station were highly correlated with one another.…”
Section: Discussionmentioning
confidence: 94%
“…In large cities, these small particles are the most harmful to human health, as they can induce pulmonary inflammation and oxidative stress, which in turn may stimulate specific transcription factors, such as nuclear factor kB, activator protein 1, chemokines, and other serum proinflammatory mediators (12). Some studies have demonstrated that exposure to high concentrations of pollutants is associated with an increased level of serum inflammatory markers in children (13,14).…”
Section: Discussionmentioning
confidence: 99%